Scope of shielded rooms - Abdugafur Khotamov; Mirsaid Mirkomilov (Genius Publishing Group, 2023)
This article reflects the effectiveness of electromagnetic shielding is achieved using honeycomb holes (waveguide filters). The air exchange system is carried out by an air conditioner, the indoor unit of which must be located outdoors and the air is cooled by means of air ducts. Air ducts are connected to the screen of the room through a dielectric insert and a waveguide filter. All power lines, fire and security alarms are filtered, wiring around the room is carried out in pipes or shielded braid.
Keywords: electromagnetic radiation; radio absorbing materials; prototype; attenuation coefficient